FITRAH MANUSIA SEBAGAI MODAL KESALEHAN INDIVIDUAL - Hudi, Saman (FKIP Universitas Islam Jember, 2019)
Discourses on human nature based on Qur'anic verses and hadith have resulted in many differences of opinion in two major areas. First, regarding the interpretation of the hadith, which positions nature in opposition to non-Islamic religions, particularly Judaism, Christianity, and Zoroastrianism, rather than Islam. In this case, a child's conversion is determined by his or her parents. Second, the interpretation of the text of the Koran Surah Al A'raf verse 172 about taking testimony regarding the existence of God in the pre-existential human soul (while saying: